Potential adverse events of fluoxetine: a real-world study based on the FAERS database - Xuezheng Gao; Xiangjun Zhou; Zhiqiang Du; Qin Zhou; Ying Jiang; Haohao Zhu (Brazilian Journal of Psychiatry)
Objective: This study aimed to mine and analyze adverse event signals of fluoxetine using the U.S. Food and Drug Administration’s Adverse Event Reporting System database. Methods: This study focused on suspected adverse drug reaction reports between the first quarter of 2004 and the second quarter of 2023 in which fluoxetine was the primary suspected drug. Four signal mining and analysis methods were employed to comprehensively assess adverse event signals. Results: A total of 19,932,732 reports were collected, of which 22,884 primarily suspected fluoxetine. Through analysis, 862 signs involving 27 system organ classes were identified. More adverse events were reported by female patients (58.81%) than male patients (26.84%), with the largest percentage being in the 18-45 year age group. The signal strength of adverse events related to pregnancy and neonatal conditions was notable, including fetal exposure during pregnancy, exposure during pregnancy, and neonatal health-related adverse events, such as atrial septal defect, premature baby, ventricular septal defect, and maternal drugs affecting the fetus. Conclusions: Although fluoxetine has been extensively approved and applied, its use in women who are pregnant or planning to conceive should be approached with caution.